Film coating of Enterolobium schomburgkii (Benth.) Benth seeds - M. M. R. Borges; C. F. Lisboa; D. G. Araújo; I. R. Teixeira; A. M. Antunes; H. S. D. Barros; P. H. C. Castro; C.S. Silva; C. R. A. Dias (Brazilian Journal of Biology, 2025)
Abstract The growing demand for native seeds in forest restoration projects highlights the importance of technical and technological knowledge in the propagation and maintenance of forest species. Seed coating can facilitate direct seeding of these species. However, although the polymer polyvinyl alcohol (PVA) and the plasticizer glycerol have been studied for coating agricultural seeds, there is a lack of information about their behavior in forest species. Therefore, the objective of this research is to evaluate the applicability of film coating using polyvinyl alcohol and glycerol on forest seeds, specifically Enterolobium schomburgkii, and evaluate its influence on germination. The first experiment determined a suitable formulation for coating, for which three concentrations of PVA (1%, 3% and 5%) and glycerol (10%, 20% and 30%) were evaluated. To evaluate the effect of coatings on germination, a control was included, totaling 40 plots. Thickness, water vapor permeability, solubility and germination tests were carried out. The combination of 5% PVA and 10% glycerol was appropriate for coating E. schomburgkii seeds due to its properties and lack of deleterious effect on germination.